Vom „Projekt im Projekt“ zur „Stadt in der Stadt“? Probleme der Governance und des Managements großer urbaner Entwicklungsvorhaben am Beispiel der Wissenschaftsstadt Belval, Luxemburg - Leick, Annick; Hesse, Markus; Becker, Tom (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
The paper explores the issue of new urban development areas from two specific perspectives: on the one hand, rather than concentrating on housing, we address the question of science and research, in particular university locations and science parks, as a central guiding principle for urban expansion. On the other hand, the paper focuses on the analysis of urban management and governance practices and, more specifically, the disjoining of large projects from their common urban planning context. Emphasis is put on the fact that such undertakings are defined as ‘projects’ and that they are subordinated to a specific management approach. Amid debates concerning large-scale urban development projects and urban governance, we develop the thesis that the risk for projects to unfold as a sort of ‘foreign matter’ in the urban realm increases as the degree to which they are subject to proven planning processes and regulatory practices diminishes. This argument will be empirically illustrated with Belval, the science city in the south of Luxembourg, which is developed ever since 2003 and whose progress is critically assessed here. The general conclusions include planning requirements for dealing with new large-scale development projects.